Decision-Making at End-of-Life for Children With Cancer: A Systematic Review and Meta-Bioethical Analysis - Juárez-Villegas, Luis Enrique; Altamirano-Bustamante, Myriam M.; Zapata-Tarrés, Marta M. (Frontiers in Oncology, 2021)
Background Evidence shows that medical education includes a variety of basic and clinical skills. Ethical and human values are not typically considered in medical school curricula, and this is evident in medical practice in certain scenarios such as decision-making at pediatric cancer patients' end of life. Methods This study explores a bioethical approach to address complex decision-making at the end of life in children and adolescents with cancer. We are a cross-functional group of scientists from several academic disciplines who conducted a systematic review of the literature using our newly developed meta-bioethical analysis and synthesis of findings. The search was carried out in five databases, resulting in 10 research papers. Following quality screening, seven articles were ultimately selected for further analysis. Results Our focus is on the state of the art to better understand the bioethical deliberation at the end of life in pediatric oncology. Here, we report a systematic review that includes (i) classification of the screened articles by the type of decision-making they use, ii) the system values that are at the core of the decision-making at the end of life, and iii) bioethical and ethical discernment queries. We conclude with a discussion regarding the best practices of ethical discernment and decision-making at the end of life. This study highlights the need to develop more research to better understand the influence and origin of these multidimensional factors determining critical decisions that define the quality of life of patients in a highly sensitive moment. Conclusion We conclude that personal aspects of the physician define their actions more than knowledge or organized structure. It is thus necessary that pediatric oncologists receive ethics and humanistic education.